The problem of space-time boundaries of culture - Shkepu, Mariia (Actual Problems of Mind, 2017)
The article is devoted to the outline of certain aspects of the problem of epistemological, social and anthropological boundaries of culture as a consequence of peculiar transformations of the basis of history in its spatio-temporal contradictions